Rapid determination of ambrisentan enantiomers by enantioselective liquid chromatography using cellulose-based chiral stationary phase in reverse phase mode - Douša, Michal; Gibala, Petr (Journal of separation science, 2012)
A sensitive, specific, and rapid high-performance liquid chromatography (HPLC) method for the determination of ambrisentan enantiomers has been developed and validated. Six chiral columns were tested in a reversed-phase system. Excellent enantioseparation with the resolution more than 2.5 was achieved on Chiralcel OZ-3R (cellulose 3-chloro-4-methylphenylcarbamate) using mixture of 20 mM sodium formate (pH 3.0) with acetonitrile (55:45; v/v). Validation of the HPLC method including linearity, limit of detection, limit of quantification, precision, accuracy, and selectivity was performed according to the International Conference on Harmonisation (ICH) guidelines. The method has an advantage of a very quick chromatographic separation (less than 6 min) and therefore is highly suitable for routine determination of (R)-ambrisentan in enantiopure active pharmaceutical ingredient (S)-ambrisentan.
Keywords: Adsorption; vysokoúčinná kapalinová chromatografie; Stereoisomerism; Pyridazines; pyridaziny; Chromatography, High Pressure Liquid; celulosa; fenylpropionáty; Cellulose; chromatografie s reverzní fází; Chromatography, Reverse-Phase; Phenylpropionates; stereoizomerie; adsorpce